Evaluasi Koordinasi Relay Arus Lebih (OCR) Dan Gangguan Tanah (GFR) Pada Gardu Induk Garuda Sakti Pekanbaru - Ridha, Khalik Al (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This study aimed to obtain the optimal setting and should be of 50 MVA transformer protection system at the substation Garuda Sakti Pekanbaru. This study uses observation, that determines which objects will be studied to evaluate the coordination of the relay in the transformer of 50 MVA substation Garuda Sakti Pekanbaru. With the data obtained as a diagram of the distribution network of the line (SUTM) substation Garuda Sakti Pekanbaru along with CB data, the transformers, relay specification OCR and GFR and tuning existing conditions relay, and additional data that support for this thesis as load data and daily etc. From the calculation results with existing data in the field is still in appropriate conditions (the difference is not too much), so it can be concluded that the overall arrangement of OCR and GFR in the field is still in good condition. OCR for relay settings and GFR in the feeder has about the same value at which the TMS for OCR and GFR each 0,154s 0,15s in calculations and in the field to OCR, and 0,103s in the calculation and in the field with 0,15s GFR, but there relay settings no longer appropriate that the relay settings and GFR OCR on the side of the entrance, where TMS and TMS = 0,3s = 0,3s in other words if there is a short circuit fault then the relay will take a long time to work. So setting relay OCR and GFR incoming side that is in the field must be set back.Keyword : OCR , GFR